2011
DOI: 10.1002/mds.23884
|View full text |Cite
|
Sign up to set email alerts
|

The Movement Disorder Society Evidence‐Based Medicine Review Update: Treatments for the non‐motor symptoms of Parkinson's disease

Abstract: The Movement Disorder Society (MDS) Task Force on Evidence-Based Medicine (EBM) Review of Treatments for Parkinson's Disease (PD) was first published in 2002 and was updated in 2005 to cover clinical trial data up to January 2004 with the focus on motor symptoms of PD. In this revised version the MDS task force decided it was necessary to extend the review to non-motor symptoms. The objective of this work was to update previous EBM reviews on treatments for PD with a focus on non-motor symptoms. Level-I (rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
607
0
29

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 917 publications
(674 citation statements)
references
References 108 publications
(195 reference statements)
9
607
0
29
Order By: Relevance
“…Cognitive impairment, autonomic dysfunction, and falls are all features of severe PD that substantially affect function and quality of life and incompletely respond to medication manipulation. 19 …”
Section: Advanced Treatmentsmentioning
confidence: 99%
“…Cognitive impairment, autonomic dysfunction, and falls are all features of severe PD that substantially affect function and quality of life and incompletely respond to medication manipulation. 19 …”
Section: Advanced Treatmentsmentioning
confidence: 99%
“…Indeed, it has been reported that a good night's sleep can improve motor symptoms in the morning in some patients with PD (32). It should be noted that the International Parkinson and Movement Disorder Society Task Force has reported that the evidence for the efficacy of melatonin is insufficient (33). However, the present study suggests that ramelteon may improve RBD as well as other sleep disturbances in patients with PD.…”
Section: Discussionmentioning
confidence: 46%
“…13 Some evidence supports the efficacy of certain treatments for depression, dementia, psychosis, constipation and sialorrhoea; however, there is insufficient evidence for efficacious treatments for other important non-motor symptoms that certainly contribute to poor quality of life, such as orthostatic hypotension, neurogenic bladder disturbance, erectile dysfunction, fatigue, insomnia and excessive daytime sleepiness. 14 Pain, the most frequent non-motor symptom of PD, may be due to central and/or peripheral mechanisms. 15,16 Manifesting as arthralgic Safinamide is a unique molecule with a novel mechanism of action.…”
Section: Recent Data On the Management Of Non-motor Symptomsmentioning
confidence: 99%